Apuntes de análisis comparativo de la legislación chilena y peruana en materia de Responsabilidad Penal de las Personas Jurídicas - Millán Gutiérrez, Iván (2018)
The regime of criminal responsibility of legal entities broke the old Latin maxim “societas delinquere non potest”. The responsibility of legal entities is now a reality in the Chilean and Peruvian legal systems, reflecting the political will to implement better practices in the relationships between the State and private entities, encouraging companies to self-regulate and control the activities of their employees and representatives.